The art of ethnic minorities’ traditional beliefs in Northwest region of Vietnam - Loi, Le Van (CENTRAL ASIA AND THE CAUCASUS, 2024)
Vietnamese culture is a culture unified in diversity from the cultures of 54 ethnic groups. The traditional religious culture of ethnic minorities is an integral part of ethnic culture and of Vietnamese culture in general. Northwest Vietnam is an area where many ethnic minorities reside with diverse and rich religious lives. Each type of traditional belief carries within it cultural values, ethics, customs, and artistic values imbued with ethnic identity. Along with the practice of traditional beliefs, the ethnic minorities in this area have preserved many unique traditional beliefs’ art forms, contributing to the distinct cultural nuances of each ethnic group and the diversity of Vietnamese culture. By ways of analysis and compilation, this article focuses on identifying the appearance and characteristics of some art forms of traditional beliefs, as well as some basic values and rolls of the art of traditional beliefs in spiritual life of ethnic minorities in Northwest Vietnam today.